Exploring a Critical Threshold in Sleep Loss on Subsequent Evening Performance, Following Two Nights Partial Sleep Restriction: A Secondary Analysis is Implementing a Post‐lunch Nap Beneficial? - Ben Joseph Edwards; Ellis Brotherton; Adrian Markov; Theresa Toussaint; Magali Giacomoni; Chloe Gallagher; Samuel Andrew Pullinger (Brain and Behavior)
ABSTRACT Purpose: We investigated sleep‐restriction (SR, two nights) on evening (5:00 p.m.) weightlifting and effects following a 1‐h nap. Thirty strength‐trained males were allocated into two groups, either 4‐h [SR4] or 3‐h sleep [SR3], retiring at either 02:30 or 03:30 p.m. and waking at 06:30 p.m. for two nights), with 5:00 p.m. grip‐strength and bench‐press; and whether performance improves at 5:00 p.m. after a 1:00 p.m. nap (0 or 60‐min). Method Both groups undertook a one‐repetition‐max (1RM) for bench press and were randomly allocated either condition (i) no (N0) then (ii) a 60‐min nap (N60). Intra‐aural temperature/profile‐of‐mood‐scores/alertness/tiredness/sleepiness values were measured at 08:00 a.m., 11:00 a.m., 2:00 p.m., and 5:00 p.m. following the two nights of SR. At 5:00 p.m., a warm‐up, right‐hand grip strength, followed by lifts (40, 60, and 80% of 1RM) for bench press with recovery occurred. A linear encoder, attached to the bar, measured peak‐power (PP), peak‐velocity (PV), displacement (D) and time‐to‐peak velocity (tPV). Grip strength was not affected by SR or nap (p > 0.005). PP and PV were lower and tPV longer in the SR4 versus SR3 group, reflecting a higher 1RM. Lower tiredness/fatigue/confusion/sleepiness and an increase in alertness in the SR4 group than SR3, reflecting effects of greater sleep loss on tiredness/alertness/sleepiness/mood. Time‐of‐day effects were shown in temperature/subjective/mood‐responses (p < 0.05), with positive modifications in sleepiness/alertness/tiredness after the 1‐h nap at 1:00 p.m. in both the SR3 an SR4 groups. Finding Improvements in PV after the 1‐h nap were only found in the SR3 condition (p = 0.029). In summary, a dose‐response of sleep loss on subjective values and mood was found (SR3 worse than SR4). But not grip‐strength or bench‐press –strength being resistant to sleep loss and a stronger cohort in the SR3 than the SR4 group. Conclusion Implementing a nap (N60) improved alertness/vigor/happiness and some strength measures (↑PV) for bench press compared to N0, but this was only effective for the SR3 condition.